A legal perspective to environmental sustainability in Saudi Arabia - Aldosari, Bader (Research Journal in Advanced Humanities, 2025)
This study presents a legal perspective on environmental sustainability in Saudi Arabia. The principal purpose of the study is to explore how the different aspects of environmental sustainability are highlighted and fostered by various laws laid down by the Saudi government and emphasized by the 2030 Saudi Vision, and to examine Saudi Arabia's environmental laws and regulations, emphasizing the Kingdom's attempts to strike a balance between environmental responsibility and economic progress. The study attempts to fulfill three main objectives: (1) exploring how environmental sustainability is supported by various laws and regulations in Saudi Arabia, (2) demonstrating the different laws and rules regulating the process of environmental sustainability in Saudi Arabia, and (3) highlighting how 2030 Saudi Vision is highly concerned with the numerous facets of environmental sustainability. Two main findings are revealed here: first, Saudi Arabia has made significant strides in creating a strong legal framework to handle environmental concerns while striking a balance between sustainability and economic growth; and second, Saudi Arabia is making great efforts to safeguard its environment for coming generations by enacting extensive environmental laws, rules, and regulations, such as those pertaining to waste management, pollution prevention, and water conservation.